Multifunctional fireproof anticorrosive paint and production process thereof

By using phosphorus-based flame retardants, modified aerogels and metal powder in multifunctional fire-resistant and corrosion coatings, carbon film and porous structures are formed, which solves the problem of insufficient performance of existing coatings in high temperature and corrosion environments, and achieves excellent fire-proof, corrosion-proof and impact-resistant effects.

CN119552549APending Publication Date: 2025-03-04HENAN SUNSHINE ANTICORROSIVE PAINTING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411728052.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing multifunctional fire-resistant and anti-corrosion coatings have shortcomings in the balance of fire-resistant, corrosion-resistant and impact-resistant properties, and it is difficult to maintain excellent performance in high temperature and corrosive environments.

Method used

Key components such as phosphorus-based flame retardants, 2-hydroxyethyl methacrylate phosphate modified aerogels, metal powders, etc. are used to form a carbon film, porous structure and dense protective layer through synergistically to block oxygen and heat, and enhance the filling and adhesion of the coating.

Benefits of technology

It significantly improves the flame retardant and corrosion resistance of the coating, improves impact resistance and high temperature resistance, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005159661610000081
    Figure BDA0005159661610000081
  • Figure BDA0005159661610000091
    Figure BDA0005159661610000091
Patent Text Reader

Abstract

The invention relates to the technical field of coatings, and particularly discloses a multifunctional fireproof anticorrosive coating and a production process thereof. The multifunctional fireproof anticorrosive paint is prepared from the following raw materials in parts by weight: 10 to 15 parts of silicone acrylic emulsion, 6 to 8 parts of phosphorus flame retardant, 12 to 15 parts of acrylic resin, 10 to 20 parts of modified aerogel, 2 to 4 parts of curing agent, 4 to 8 parts of metal powder, 5 to 8 parts of bentonite and 25 to 28 parts of solvent, and the modified aerogel is aerogel prepared by modifying methacrylic acid-2-hydroxyethyl phosphate; the preparation method comprises the following steps: respectively adding the phosphorus flame retardant, the bentonite, the acrylic resin and the metal powder into the silicone acrylic emulsion, adding one part of the solvent, stirring, mixing, grinding, adding the modified aerogel and the curing agent, continuously stirring, adding the other part of the solvent, uniformly stirring and mixing, filtering by using a screen, and packaging. The composition provided by the invention has the advantages of good fireproof performance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coating technology, and more specifically, to a multifunctional fireproof and anticorrosive coating and a production process thereof. Background Art

[0002] Multifunctional fireproof and anticorrosive coating is a new type of coating that integrates multiple properties such as fireproofing, corrosion resistance, weather resistance, and impact resistance. It has a wide range of applications, including but not limited to the exterior and interior decoration of industrial plants, commercial buildings, and residential buildings, as well as the protection of facilities in the petroleum, chemical, and electric power industries. This coating, through scientific formula design and unique production process, can give the coating excellent fire retardant ability, effectively delay the spread of fire, and show excellent durability and stability in corrosive environments. In addition, it also has good impact resistance, can resist the impact and wear of external objects, and extend the service life of the coating. With the continuous improvement of people's awareness of building safety and environmental protection, multifunctional fireproof and anticorrosive coatings have become an indispensable and important part of modern buildings and industrial facilities.

[0003] At present, the fire-retardant and anti-corrosion coatings available on the market mostly use traditional inorganic or organic materials as the main film-forming substances, and enhance the performance of the coatings by adding auxiliary ingredients such as flame retardants and preservatives. However, these coatings often have some shortcomings. For example, although some inorganic coatings have good fire resistance, their impact resistance is relatively weak, and they are prone to cracking and falling off during long-term use. Although organic coatings have good flexibility and impact resistance, their fire resistance and anti-corrosion properties are often difficult to guarantee in high temperature and corrosive environments.

[0004] With respect to the above-mentioned related technologies, the inventors believe that the performance of the multifunctional fire-retardant and anti-corrosion coatings currently on the market still needs to be improved, especially in terms of the balance between fire retardancy, corrosion resistance and impact resistance, which needs to be further optimized. Summary of the invention

[0005] In order to improve the fireproof, anti-corrosion and impact resistance of the coating, the present application provides a multifunctional fireproof and anti-corrosion coating and a production process thereof.

[0006] In the first aspect, the present application provides a multifunctional fire retardant and anticorrosive coating, which adopts the following technical solution: A multifunctional fireproof and anticorrosive coating, comprising the following raw materials in parts by weight: 10-15 parts of silicone-acrylic emulsion, 6-8 parts of phosphorus flame retardant, 12-15 parts of acrylic resin, 10-20 parts of modified aerogel, 2-4 parts of curing agent, 4-8 parts of metal powder, 5-8 parts of bentonite and 25-28 parts of solvent, wherein the modified aerogel is an aerogel modified by 2-hydroxyethyl methacrylate phosphate.

[0007] By adopting the above technical scheme, the phosphorus-based flame retardant can catalyze the dehydration of polymer materials such as acrylic resin into carbon, form a carbon film, effectively block oxygen, change the combustion process of the polymer, and thus exert a flame retardant effect. At the same time, in the gas phase, the PO· free radicals generated by the thermal decomposition of the phosphorus-based flame retardant can also effectively quench the combustion free radicals and inhibit the continuation of the combustion chain reaction. The honeycomb porous structure of the aerogel modified with 2-hydroxyethyl methacrylate phosphate has been further optimized. This structure enables the material to better absorb and disperse stress when subjected to external forces, thereby improving the brittleness and poor impact resistance caused by acrylic resin. At the same time, the modified aerogel has a lower thermal conductivity, which can effectively prevent heat transfer. The excellent thermal insulation performance enables the coating to maintain a low surface temperature in a high temperature environment, thereby further improving the high temperature resistance of the coating and improving the fire resistance.

[0008] The modified aerogel also has good filling and adhesion properties. It can tightly fill the tiny pores and cracks in the coating, improving the density and durability of the coating. This dense structure can effectively prevent the penetration of harmful substances such as moisture and oxygen, and improve the corrosion resistance of the coating.

[0009] The silicone-acrylic emulsion, phosphorus flame retardant, acrylic resin and 2-hydroxyethyl methacrylate phosphate modified aerogel in the formula work synergistically to effectively isolate oxygen and heat transfer, prevent the penetration and damage of harmful components, and further add metal powder to enhance the high temperature resistance and corrosion resistance of the coating, achieving excellent fire prevention and anti-corrosion effects as a whole, and significantly improving the flame retardant properties and anti-corrosion capabilities of the coating.

[0010] Optionally, the modified aerogel preparation comprises the following steps: Methyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, acetic acid and deionized water are mixed in a water bath at 40-60° C. and stirred for reaction. During the process, 2-hydroxyethyl methacrylate phosphate is added and mixed. The stirring reaction is continued for 1-2 hours. After the reaction is completed, the product is freeze-dried to obtain the modified aerogel.

[0011] By adopting the above technical solution, the porous aerogel has excellent thermal insulation performance, effectively preventing further heat transfer, and introducing the functional monomer of 2-hydroxyethyl methacrylate phosphate to cover the surface of aerogel particles with high surface energy, reducing its surface energy, and the phosphate group thereon can form hydrogen bonds with the silicon hydroxyl groups in the silica sol, and the hydroxyethyl group can react with the hydroxyl, carboxyl and other functional groups in the resin matrix, which not only enhances the interfacial bonding force between the aerogel and the resin matrix, but also enables the aerogel to be more evenly dispersed in the resin matrix, effectively avoiding the occurrence of agglomeration. The evenly dispersed aerogel can give full play to its excellent properties such as thermal insulation, heat preservation, and adsorption, and at the same time form a tighter overall structure with the resin matrix, thereby improving the overall performance of the coating, and making the coating have more beneficial thermal stability, better mechanical strength and stronger corrosion resistance.

[0012] Optionally, in the preparation process of the modified aerogel, the weight ratio of methyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and 2-hydroxyethyl methacrylate phosphate is 1:0.4-0.6:1.4-1.8.

[0013] By adopting the above technical solution, 2-hydroxyethyl methacrylate phosphate can be more evenly distributed on the surface of silica sol particles as a modifier, and the two are tightly combined through chemical reaction to form a more uniform and fine porous structure. This refined porous structure is conducive to increasing the specific surface area and porosity of aerogel, thereby improving its thermal insulation performance.

[0014] Optionally, divinyltetramethyldisilazane is further added during the process of preparing the modified aerogel, and the weight ratio of the divinyltetramethyldisilazane to methyltrimethoxysilane is 0.3-0.9:1.

[0015] By adopting the above technical scheme, the hydrolysis-stable group CH2=CH-Si-(CH3)2 in silazane can react with the hydroxyl group in the silica sol, replacing the hydrophilic group hydroxyl group in the sol with the hydrophobic group, thereby obtaining a silica sol with hydrophobic groups on the surface, and the introduced vinyl group has a certain polarity, which can interact with the polar groups on other substrates in the raw materials, thereby enhancing the bonding force between the silica sol and the substrate, and further improving the overall performance of the coating.

[0016] Optionally, the density of the metal powder is 1.5-2.6 g / cm 3 between.

[0017] By adopting the above technical solution, metal powders matching the density of the coating substrate are selected to ensure that the metal powders can be firmly attached to the substrate and are not easy to fall off, thereby improving the corrosion resistance of the coating. At the same time, metal powders within this density range can be evenly dispersed in the coating to form a dense protective layer, isolating the penetration of external harmful components and improving the corrosion resistance of the coating.

[0018] Optionally, the raw materials further include 8-12 parts of chloroether resin.

[0019] By adopting the above technical solution, the chloroether resin and the acrylic resin have good compatibility, and the isobutyl ether long chain group therein exists as a branch chain of the polymer chain, so that the polymer polymer is not easy to be stacked tightly, the crystallinity is reduced, and the macroscopic performance is that the flexibility of the polymer is enhanced, which effectively improves the problem of poor flexibility of the acrylic resin and further improves the impact resistance of the coating. At the same time, the stability of the chlorine atoms and the presence of non-reactive double bonds in the chloroether resin make it resistant to corrosion by a variety of acids, alkalis, salts and other chemicals, and the addition of synergistic effects with the acrylic resin further enhances the corrosion resistance of the coating.

[0020] Optionally, the curing agent is an amino resin.

[0021] By adopting the above technical solution, the amino resin curing agent can form a cross-linked structure with the resin in the coating to form a dense protective layer, which can effectively isolate the substrate from the external environment, such as moisture, oxygen, acid and alkali, etc. Therefore, the coating using amino resin as a curing agent has excellent corrosion resistance.

[0022] In the second aspect, the present application provides a production process for a multifunctional fire retardant and anticorrosive coating, which adopts the following technical solution: A production process of a multifunctional fireproof and anticorrosive coating comprises the following steps: Phosphorus flame retardant, bentonite, acrylic resin and metal powder are respectively added to silicone acrylic emulsion, a part of solvent is added, stirred, mixed and ground, modified aerogel and curing agent are added and stirred continuously, another part of solvent is added, stirred and mixed, filtered through a sieve and then packaged to obtain the product.

[0023] In summary, this application has the following beneficial effects: 1. Due to the synergistic effect of key components such as phosphorus flame retardants, 2-hydroxyethyl methacrylate phosphate modified aerogel, and metal powder, this application effectively isolates the transfer of oxygen and heat and prevents the infiltration of harmful components, thereby achieving excellent fire prevention and anti-corrosion effects. Phosphorus flame retardants can catalyze the dehydration of polymers into carbon, forming a carbon film to block oxygen, while the porous structure and low thermal conductivity of the modified aerogel further enhance the high temperature resistance and heat insulation performance of the coating. The addition of metal powder enhances the high temperature resistance and corrosion resistance of the coating, and significantly improves the flame retardant performance and anti-corrosion ability of the coating as a whole.

[0024] 2. In the present application, the honeycomb porous structure of the aerogel is optimized by introducing functional monomers such as 2-hydroxyethyl methacrylate phosphate, thereby improving its filling and adhesion properties and making the coating more dense and durable. At the same time, this modification also enhances the interfacial bonding force between the aerogel and the resin matrix, avoiding the occurrence of agglomeration, thereby giving full play to the excellent performance of the aerogel.

[0025] 3. The chloroether resin added in this application has good compatibility with acrylic resin and enhances the flexibility of the coating. The isobutyl ether long-chain group in the chloroether resin makes it difficult for the polymer macromolecule to be stacked tightly, reduces the crystallinity, and thus improves the flexibility and impact resistance of the coating. At the same time, the presence of chlorine atoms and non-reactive double bonds in the chloroether resin enables it to resist corrosion from a variety of chemicals, and synergizes with the acrylic resin to further enhance the corrosion resistance of the coating. DETAILED DESCRIPTION

[0026] The present application is further described in detail below with reference to the embodiments.

[0027] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0028] Acrylic resin was purchased from Fahrenheit (Guangdong) New Material Technology Co., Ltd., with a viscosity of 200-800 mPa.s and a model number of ACR-S6178; silicone-acrylic emulsion was purchased from Jinan Zi'an Chemical Co., Ltd., with a brand number of 50 and an active ingredient content of 99.5%.

[0029] Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified aerogel, the preparation of which comprises the following steps: 20 kg of methyltrimethoxysilane, 8 kg of γ-mercaptopropyltriethoxysilane, 0.6 kg of acetic acid and 7 kg of deionized water were mixed and heated to 50° C. in a water bath and stirred for reaction. During the process, 32 kg of 2-hydroxyethyl methacrylate phosphate was added and mixed. The stirring reaction was continued for 1.5 hours. After the reaction was completed, the product was placed in a freeze dryer and freeze-dried to obtain the modified aerogel.

[0030] Preparation Example 2 A modified aerogel, the preparation of which comprises the following steps: 20 kg of methyltrimethoxysilane, 10 kg of γ-mercaptopropyltriethoxysilane, 0.6 kg of acetic acid and 7 kg of deionized water were mixed and heated to 40° C. in a water bath and stirred for reaction. During the process, 28 kg of methyl acrylate-2-hydroxyethyl phosphate was added and mixed. The stirring reaction was continued for 1 hour. After the reaction was completed, the product was placed in a freeze dryer and freeze-dried to obtain the modified aerogel.

[0031] Preparation Example 3 A modified aerogel, the preparation of which comprises the following steps: 20 kg of methyltrimethoxysilane, 12 kg of γ-mercaptopropyltriethoxysilane, 0.6 kg of acetic acid and 7 kg of deionized water were mixed and heated to 60° C. in a water bath and stirred for reaction. During the process, 36 kg of methyl acrylate-2-hydroxyethyl phosphate was added and mixed, and the stirring reaction was continued for 2 hours. After the reaction was completed, the product was placed in a freeze dryer and freeze-dried to obtain the modified aerogel.

[0032] Preparation Example 4 A modified aerogel, which is different from Preparation Example 1 in that divinyltetramethyldisilazane is further added in this Preparation Example, and the preparation comprises the following steps: 20 kg of methyltrimethoxysilane, 8 kg of γ-mercaptopropyltriethoxysilane, 0.6 kg of acetic acid and 7 kg of deionized water were mixed and heated to 50° C. in a water bath and stirred for reaction. During the process, 32 kg of 2-hydroxyethyl methacrylate phosphate and 12 kg of divinyltetramethyldisilazane were added and mixed. The stirring reaction was continued for 1.5 hours. After the reaction was completed, the product was placed in a freeze dryer and freeze-dried to obtain the modified aerogel.

[0033] Preparation Example 5 A modified aerogel, which is different from Preparation Example 1 in that divinyltetramethyldisilazane is further added in this Preparation Example, and the preparation comprises the following steps: 20 kg of methyltrimethoxysilane, 8 kg of γ-mercaptopropyltriethoxysilane, 0.6 kg of acetic acid and 7 kg of deionized water were mixed and heated to 50° C. in a water bath and stirred for reaction. During the process, 32 kg of 2-hydroxyethyl methacrylate phosphate and 6 kg of divinyltetramethyldisilazane were added and mixed. The stirring reaction was continued for 1.5 hours. After the reaction was completed, the product was placed in a freeze dryer and freeze-dried to obtain the modified aerogel.

[0034] Preparation Example 6 A modified aerogel, which is different from Preparation Example 1 in that divinyltetramethyldisilazane is further added in this Preparation Example, and the preparation comprises the following steps: 20 kg of methyltrimethoxysilane, 8 kg of γ-mercaptopropyltriethoxysilane, 0.6 kg of acetic acid and 7 kg of deionized water were mixed and heated to 50° C. in a water bath and stirred for reaction. During the process, 32 kg of 2-hydroxyethyl methacrylate phosphate and 18 kg of divinyltetramethyldisilazane were added and mixed. The stirring reaction was continued for 1.5 hours. After the reaction was completed, the product was placed in a freeze dryer and freeze-dried to obtain the modified aerogel.

[0035] Comparative Preparation Example 1 An aerogel, the preparation of which comprises the following steps: 20 kg of methyltrimethoxysilane, 8 kg of γ-mercaptopropyltriethoxysilane, 0.6 kg of acetic acid and 7 kg of deionized water were mixed and heated to 50° C. in a water bath and stirred for reaction for 1.5 h. After the reaction was completed, the product was placed in a freeze dryer for freeze drying to obtain the aerogel. Example

[0036] Example 1 A multifunctional fireproof and anticorrosive coating, the production process steps are as follows: 7 kg of aluminum tripolyphosphate, 6.5 kg of bentonite, 13.5 kg of acrylic resin and 6 kg of aluminum powder (metal powder) were added to 15 kg of silicone acrylic emulsion, 12 kg of propylene glycol butyl ether was added, stirred and mixed, and ground to a fineness of <50 μm, 15 kg of modified aerogel and 3 kg of urea-formaldehyde resin (curing agent) were added and continued to be stirred, 13 kg of propylene glycol butyl ether was added, stirred and mixed, and the fire retardant and anticorrosive coating was obtained after filtering with an 80-mesh sieve and packaging; the modified aerogel was prepared in Preparation Example 1, and the metal powder was selected as aluminum powder with a density of 2.1 g / cm 3 .

[0037] Example 2 A multifunctional fireproof and anticorrosive coating, the production process steps are as follows: 8 kg of aluminum tripolyphosphate, 5 kg of bentonite, 12 kg of acrylic resin and 8 kg of aluminum powder (metal powder) were added to 12.5 kg of silicone-acrylic emulsion, 11.5 kg of propylene glycol butyl ether was added, stirred and mixed, and ground to a fineness of <50 μm, 20 kg of modified aerogel and 2 kg of urea-formaldehyde resin (curing agent) were added and continued to be stirred, 16 kg of propylene glycol butyl ether was added, stirred and mixed, and the fire retardant and anticorrosive coating was obtained after filtering with an 80-mesh sieve and packaging; the modified aerogel was prepared in Preparation Example 2, and the metal powder was selected as aluminum powder with a density of 2.1 g / cm 3 .

[0038] Example 3 A multifunctional fireproof and anticorrosive coating, the production process steps are as follows: 6 kg of aluminum tripolyphosphate, 8 kg of bentonite, 15 kg of acrylic resin and 4 kg of aluminum powder (metal powder) were added to 10 kg of silicone acrylic emulsion, 14 kg of propylene glycol butyl ether was added, stirred and mixed, and ground to a fineness of <50 μm, 10 kg of modified aerogel and 4 kg of urea-formaldehyde resin (curing agent) were added and continued to be stirred, 14 kg of propylene glycol butyl ether was added, stirred and mixed, and the fire retardant and anticorrosive coating was obtained after filtering with an 80-mesh sieve and packaging; the modified aerogel was prepared in Preparation Example 3, and the metal powder was selected as aluminum powder with a density of 2.1 g / cm 3 .

[0039] Example 4 A multifunctional fireproof and anticorrosive coating, which is different from Example 1 in that the modified aerogel used in this example is prepared in Preparation Example 4.

[0040] Example 5 A multifunctional fireproof and anticorrosive coating, which is different from Example 1 in that the modified aerogel used in this example is prepared in Preparation Example 5.

[0041] Example 6 A multifunctional fireproof and anticorrosive coating, which is different from Example 1 in that the modified aerogel used in this example is prepared in Preparation Example 6.

[0042] Example 7 A multifunctional fireproof and anticorrosive coating, which is different from Example 1 in that the metal powder used in this example is iron powder with a density of 7.8 g / cm 3 .

[0043] Example 8 A multifunctional fireproof and anticorrosive coating, which is different from Example 1 in that 10 kg of chloroether resin is further added in this embodiment, and the preparation comprises the following steps: 7 kg of aluminum tripolyphosphate, 6.5 kg of bentonite, 13.5 kg of acrylic resin and 6 kg of aluminum powder (metal powder) were added to 15 kg of silicone acrylic emulsion, 12 kg of propylene glycol butyl ether was added, stirred and mixed, and ground to a fineness of <50 μm, 10 kg of chloroether resin, 15 kg of modified aerogel and 3 kg of urea-formaldehyde resin (curing agent) were added and continued to be stirred, 13 kg of propylene glycol butyl ether was added, stirred and mixed, and the fire retardant and anticorrosive coating was obtained after filtering with an 80-mesh sieve; the modified aerogel was prepared in Preparation Example 1, and the metal powder was selected as aluminum powder with a density of 2.1 g / cm 3 .

[0044] Example 9 A multifunctional fireproof and anticorrosive coating, which is different from Example 8 in that 8 kg of chloroether resin is added in this example.

[0045] Example 10 A multifunctional fireproof and anticorrosive coating, which is different from Example 8 in that 12 kg of chloroether resin is added in this example.

[0046] Comparative Example Comparative Example 1 A multifunctional fireproof and anticorrosive coating, which is different from Example 1 in that the aerogel in this comparative example is not modified and is prepared in Comparative Preparation Example 1.

[0047] Comparative Example 2 A multifunctional fireproof and anticorrosive coating, which is different from Example 1 in that no modified aerogel is added in this comparative example.

[0048] Comparative Example 3 A multifunctional fireproof and anticorrosive coating, which is different from Example 1 in that no metal powder is added in this comparative example.

[0049] Performance testing Detection method / test method Impact strength: Use a spray gun to spray the coating on a Q235 steel plate to prepare a coating sample with a thickness of 50μm. After it is completely cured, place it in the air for curing for 48 hours, and then test its impact resistance according to GB / T1732-2020 "Determination of impact resistance of paint film"; Salt water resistance test: The test is carried out with reference to GB / T1771-2007. The test solution is a NaCl solution with a mass concentration of 3.5wt%. All the edge-sealed samples are immersed in the test solution, and the water temperature is maintained at about 23°C. Regularly observe and record the peeling, rust and other phenomena on the surface of the paint film for 20 days; Thermal conductivity: The thermal conductivity of the coating is obtained by testing according to the ASTME1530 coating thermal conductivity test standard; Fire resistance: The fire resistance of the fireproof board is tested according to the burning dripping test of GB / T20284-2006.

[0050] Table 1 Experimental test results Combining Examples 1-3 and Comparative Example 1 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 1, indicating that the modification of aerogel is beneficial to the further optimization of its microporous structure, which not only further improves the impact resistance of the coating, but also has a lower thermal conductivity, effectively preventing heat transfer and improving the fire retardant performance of the coating.

[0051] Combining Examples 1-3 and Comparative Example 2 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 2. Without the addition of aerogel, the impact resistance is greatly reduced, indicating that the presence of aerogel can absorb the stress of decomposition, thereby further improving the impact resistance of the coating.

[0052] Combining Examples 1-3 and Comparative Example 3 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 3, indicating that adding metal powder to the coating of the present application can enhance the fire resistance of the coating, so that the coating can be used for a long time in a high temperature environment without being damaged.

[0053] Combining Examples 1-6 and Table 1, it can be seen that the experimental data of Examples 4-6 are better than those of Examples 1-3, indicating that adding divinyltetramethyldisilazane in the process of modifying aerogel can produce hydrophobic aerogel, and the introduced functional groups can further improve the impact strength and corrosion resistance of the coating.

[0054] Combining Example 1 with Example 7 and Table 1, it can be seen that the experimental data of Example 1 are better than those of Example 7, indicating that the compatibility between the raw materials can be improved by further limiting the density of the metal powder. At the same time, the metal powder of appropriate density can be evenly dispersed in the coating to form a dense protective layer, thereby improving the corrosion resistance of the coating.

[0055] Combining Example 1 with Examples 8-10 and Table 1, it can be seen that the experimental data of Examples 8-10 are better than those of Example 1, indicating that the addition of chloroether resin to the coating can not only enhance the flexibility and impact resistance of the coating, but also, due to the presence of chlorine atoms and non-reactive double bonds in the chloroether resin, it can synergize with the acrylic resin to further enhance the corrosion resistance of the coating.

[0056] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A multifunctional fireproof and anticorrosive coating, characterized in that: The composition comprises the following raw materials in parts by weight: 10-15 parts of silicone-acrylic emulsion, 6-8 parts of phosphorus flame retardant, 12-15 parts of acrylic resin, 10-20 parts of modified aerogel, 2-4 parts of curing agent, 4-8 parts of metal powder, 5-8 parts of bentonite and 25-28 parts of solvent, wherein the modified aerogel is an aerogel modified by 2-hydroxyethyl methacrylate phosphate.

2. The multifunctional fireproof and anticorrosive coating according to claim 1, characterized in that: The modified aerogel preparation comprises the following steps: Methyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, acetic acid and deionized water are mixed in a water bath at 40-60° C. and stirred for reaction. During the process, 2-hydroxyethyl methacrylate phosphate is added and mixed. The stirring reaction is continued for 1-2 hours. After the reaction is completed, the product is freeze-dried to obtain the modified aerogel.

3. A multifunctional fireproof and anticorrosive coating according to claim 2, characterized in that: In the preparation process of the modified aerogel, the weight ratio of methyltrimethoxysilane, gamma-mercaptopropyltriethoxysilane and 2-hydroxyethyl methacrylate phosphate is 1:0.4-0.6:1.4-1.

8.

4. The multifunctional fireproof and anticorrosive coating according to claim 2, characterized in that: In the process of preparing the modified aerogel, divinyltetramethyldisilazane is also added, and the weight ratio of the added divinyltetramethyldisilazane to methyltrimethoxysilane is 0.3-0.9:

1.

5. The multifunctional fireproof and anticorrosive coating according to claim 1, characterized in that: The density of the metal powder is 1.5-2.6 g / cm 3 between.

6. The multifunctional fireproof and anticorrosive coating according to claim 1, characterized in that: The raw materials also include 8-12 parts of chloroether resin.

7. The multifunctional fireproof and anticorrosive coating according to claim 1, characterized in that: The curing agent is amino resin.

8. A production process of the multifunctional fire retardant and anticorrosive coating according to any one of claims 1 to 7, characterized in that: The steps include: Phosphorus flame retardant, bentonite, acrylic resin and metal powder are respectively added to silicone acrylic emulsion, a part of solvent is added, stirred, mixed and ground, modified aerogel and curing agent are added and stirred continuously, another part of solvent is added, stirred and mixed, filtered through a sieve and then packaged to obtain the product.

Citation Information

Patent Citations

  • Aerogel-containing water-based expansion type fire-retardant coating and preparation method thereof

    CN106479297A

  • Preparation method of modified silica aerogel, and modified silica aerogel

    CN111592329A

  • Flame-retardant ethylene propylene diene monomer rubber sleeve for cable and preparation method thereof

    CN114874556A

  • Water-based hybrid acrylic flame-retardant resin composition and preparation method thereof

    CN116716006A

  • Preparation method and application of aerogel composite phase change thermal insulation material

    CN117964939A